Demographic Factors and Community Knowledge of Desa Siaga for Enhanching Maternal and Neonatal Health - Vinami Yulian; Sri Lestari; Wachidah Yuniartika; Sulastri Sulastri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Community knowledge in health empowerment strategies is a crucial element for the success of health programmes. However, many factors influence the level of public knowledge about a programme. This study aims to identify the relationship between demographic factors such as gender, age, education, and occupation, and the level of community knowledge about the Desa SIAGA programme as a community empowerment approach to improve maternal and neonatal health. This research employs a descriptive correlational design with a quantitative survey method. The study involved 107 respondents from Desa Jati, Sukoharjo District, using a simple random sampling technique. The data was collected through a questionnaire survey containing questions to explore the public's knowledge about the SIAGA Village program to improve maternal and neonatal health. The collected data was then analyzed using bivariate analysis and tested using the Pearson Product Moment. The results indicate that the majority of respondents have sufficient knowledge about the Desa SIAGA programme. Age and gender were found to have a significant relationship with knowledge level, with older age and female gender being associated with better knowledge. In contrast, no significant relationship was found between education level and occupation with the level of knowledge about the Desa SIAGA programme. These findings highlight the importance of more intensive outreach and community-based approaches to improve public understanding of the Desa SIAGA programme, particularly among older age groups and men.